Influencia de la densidad de corriente y de la concentración de ácido crómico sobre el espesor y adherencia de la capa de cromo decorativo en el acero ASTM A36 previamente cobreado y niquelado - Garcia Constantino, Luis Antonio (2017)
In this research the influence of the current density and the concentration of chromic acid on the thickness and adhesion of the layer of chromium in the steel ASTM A36 previously copper plating and nickel, in the Laboratory of coatings electrolysis studied UNT, in order to increase knowledge of decorative chrome steel specifically made on ASTM A36. Current density variable was evaluated in levels of 8, 14 and 20 A/dm2, the variable concentration of chromic acid was evaluated in levels 170, 270 and 370 g/L. Also, 3 replicates was performed, making a total of 27 tests. Each specimen had an area of 0.083 dm2. The results indicate that a current density of 14 A/dm2 and a concentration of chromic acid of 170 g/L and the best thickness of the adhesion layer of chromium is 100% are obtained. It is concluded that as the current density increases, the decorative chrome layer thickness increases. On the other hand, as the concentration of chromic acid decreases, the thickness of the decorative chromium layer increases, in the case of adhesion as the current density increases, the percentage of adhered area decreases. Finally, at a 95% confidence level, the analysis of variance ratifies that the 2 variables under study do have significant influence; while the interaction only influences significantly on the thickness.